Analisis Fenomena Serangan Fajar melalui persepektif Al-Qur’an dan Hukum Negara Indonesia - Naila Abidah; Muhammad Rifa’i Subhi (ejournal.nurulqadim.ac.id, 2024)
The Qur'an, Islam's holy book, emphasizes the importance of justice, compassion, and the protection of life. The law prohibits the taking of innocent lives and emphasizes the need for self-defense only when there is a legitimate threat to a person's life or property. In the context of the dawn attacks, the Qur'anic perspective states that such attacks are morally and ethically wrong, as they involve the deliberate targeting of innocent people, and this is prohibited by the Qur'an. Meanwhile, Indonesian state law also explains that dawn attacks or money politics are prohibited acts because this is a form of corruption. General elections are a form of expression of the people's rights and sovereignty which must be held directly, publicly, freely, secretly, honestly and fairly. This needs to be well realized in order to realize the context of a democratic country based on Pancasila and law. In conclusion, the phenomenon of early morning attacks is a serious concern that threatens the security and stability of society. From the Koran's perspective, such attacks are morally and ethically wrong, because they deliberately target innocent people. Indonesian law also prohibits the taking of innocent lives and emphasizes the importance of self-defense. Therefore, it is important for law enforcement agencies and the public to work together to prevent and investigate such attacks, ensuring that those responsible are held accountable for their actions.